2011
DOI: 10.2106/jbjs.j.00943
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Growth of Denervated Muscle Contributes to Contracture Formation Following Neonatal Brachial Plexus Injury

Abstract: Injury of the upper trunk of the brachial plexus leads to impaired growth of the biceps and brachialis muscles, which are responsible for elbow flexion contractures, and impaired growth of the subscapularis muscle, which correlates with internal rotation contracture of the shoulder. Shoulder muscle imbalance alone causes neither subscapularis shortening nor internal rotation contracture. Impaired muscle growth cannot be explained solely by absence of functioning satellite cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
127
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 28 publications
17
127
2
Order By: Relevance
“…Once the controlling nerve is injured, the controlled muscle is doomed to show some histological changes such as a less weight, thinned muscle fibers and more collagen fibers (Nikolaou et al, 2011). In the present study, the activity of SCs began to increase obviously at 2 w after denervation, and the number of SCs began to increase noticeably at 3 w; but such increase stopped at 2 months, and the number of SCs began to show a rapid decrease.…”
Section: Discussionsupporting
confidence: 42%
“…Once the controlling nerve is injured, the controlled muscle is doomed to show some histological changes such as a less weight, thinned muscle fibers and more collagen fibers (Nikolaou et al, 2011). In the present study, the activity of SCs began to increase obviously at 2 w after denervation, and the number of SCs began to increase noticeably at 3 w; but such increase stopped at 2 months, and the number of SCs began to show a rapid decrease.…”
Section: Discussionsupporting
confidence: 42%
“…The incidence of significant elbow flexion contractures in BPBP may be greater than clinicians perceive, and prevalence increases with patient age [31]. Nikolaou has shown that functional shortening of denervated muscle plays a primary role in contracture pathogenesis [32]. However, the mechanism of contracture development in denervated muscle remains unanswered [33,34].…”
Section: Natural Historymentioning
confidence: 99%
“…Although the exact mechanism is unknown, denervation of the upper limb during the neonatal period leads to impaired growth and eventual contracture of the affected muscles 1 . As the neonatal glenohumeral joint is entirely cartilaginous, these contractures can lead to altered joint mechanics and eventually to irreversible joint deformity.…”
mentioning
confidence: 99%